Bioactive strawberry fruit (Arbutus unedo L.) extract remedies paraquat-induced neurotoxicity in the offspring prenatally exposed rats - Lhaj, Zakaria Ait; Ibork, Hind; El Idrissi, Sara; Lhaj, Farida Ait; Sobeh, Mansour; Mohamed, Wael Mohamed Yousef; Alamy, Meryem; Taghzouti, Khalid; Abboussi, Oualid (Frontiers Media S.A., 2023)
Background: Paraquat (1,1′-dimethyl-4-4′-bipyridinium dichloride) exposure is well-established as a neurotoxic agent capable of causing neurological deficits in offspring. This study aimed to investigate therapeutic effects of Arbutus unedo L. aqueous extract (AU) against paraquat (PQ) exposure.